The Influence of Incentives and Career Development on Employee Retention - Aulia, Zahwa Hawa; Irawanto, Dodi Wirawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to measure the influence of incentives and career development on employee retention in the Marketing Division of PT GDN Jakarta Center. Design/Methodology/Approach – This study employs a quantitative research approach. A total of 89 employees from the Marketing Division were selected using purposive sampling, with the sample size determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 27 for Mac. Findings – The results show that incentives have a positive and significant effect on employee retention, and career development also has a positive and significant effect on employee retention. Furthermore, incentives and career development simultaneously have a significant influence on employee retention. These findings indicate that improving incentive systems and career development opportunities can support workforce stability and reduce employee turnover. Originality/Value This study provides empirical evidence on the simultaneous influence of incentives and career development on employee retention within a corporate marketing division. The findings offer practical insights for designing targeted HR strategies that effectively support retention efforts in similar organizational contexts.